Automatic cat feeder / Nor Fatin Amirah Mohd Rozali Yusof and Nooribtisam Balqis Azhar - Mohd Rozali Yusof, Nor Fatin Amirah; Azhar, Nooribtisam Balqis (2016)
The construction of this invention is intended to produce a machine that automatically feed cat using ATmega368 microcontroller. It is a main controller which is placed at objective is to solve problems that occur as factors cat feeding that are not systematically, to protect and help the stray cats and create a tool that is more systematic and more practical. Development of this project involves electronic and electrical. To control the setting time, electronic devices such as the microcontroller is used. The reservoir bowl of food is place to facilitate eating pets. Overall, this device can be useful for pct owner and consumer itself. Several other methods have been used as reference such as previous studies and also the cat food feeder in the market and that have been produced by certain individuals. With the development of this invention indirectly can become an innovation to the construction of landscape in the future.